Witchcraft - Gibson, Marion, author.
1 online resource (200 pages)
Keywords: Witchcraft: The Basics is an accessible and engaging introduction to the scholarly study of witchcraft, exploring the phenomenon of witchcraft from its earliest definitions in the Middle Ages through to its resonances in the modern world. Through the use of two case studies, this book delves into the emergence of the witch as a harmful figure within western thought and traces the representation of witchcraft throughout history, analysing the roles of culture, religion, politics, gender and more in the evolution and enduring role of witchcraft. Key topics discussed within the book include:?Scholarly approaches to witchcraft through timeThe role of language in creating and shaping the concept of witchcraftThe laws and treatises written against witchcraftThe representation of witchcraft in early modern literature The representation of witchcraft in recent literature, TV and filmThe relationship between witchcraft and paganismWith an extensive further reading list, summaries and questions to consider at the end of each chapter, Witchcraft: The Basics is an ideal introduction for anyone wishing to learn more about this controversial issue in human culture, which is still very much alive today.